Public Engagement Through Programming in Archives: A Systematic Review of Activities and Resultant Outcomes - Josiline Chigwada; Mthokozisi Masumbika Ncube; Patrick Ngulube (Information, 2025)
Archives have the potential to contribute to national development by preserving historical records and providing access to information. However, their impact is constrained by ineffective outreach strategies, insufficient institutional investment, and low public visibility. Public programming has been used as a strategic approach to bridge the gap between archival institutions and their user communities through engagement initiatives. Therefore, the objective of this study was to systematically review and analyse the diverse public programming activities undertaken by archival institutions globally and to identify the resultant outcomes of these engagements. To achieve this, the study employed a systematic literature review methodology, examining scholarly publications to synthesise existing evidence on public engagement in archives, thereby providing a comprehensive overview of current practices and their demonstrated impacts. The systematic review was conducted in accordance with PRISMA guidelines, utilising a two-stage selection process involving a search of six databases and four specialised journals. This search yielded 39 publications that met the inclusion criteria. Methodological rigour was evaluated using the CASP checklist. The results from the study indicated that exhibitions, educational programmes, community outreach, and digital initiatives were the most common public programming strategies. These activities enhance public awareness, increase accessibility, and foster community engagement. Despite the availability of various public programming activities, challenges such as inadequate funding, lack of digital infrastructure, and bureaucratic constraints hinder their effectiveness. The need for structured outreach strategies, institutional support, and the integration of emerging technologies to optimise public programming in archives is emphasised. The findings contribute to improving archival accessibility and user engagement in a rapidly evolving digital landscape.